Materials for stem cell factories of the future - Celiz, Adam D.; Smith, James G.W.; Langer, Robert; Anderson, Daniel G.; Barrett, David A.; Winkler, David A.; Davies, Martyn C.; Young, Lorraine E.; Denning, Chris; Alexander, Morgan R. (Nature Publishing Group, 2014)
The materials community is now identifying polymeric substrates that could permit translation of human pluripotent stem cells (hPSCs) from lab-based research to industrial scale biomedicine. Well defined materials are required to allow cell banking and to provide the raw material for reproducible differentiation into lineages for large scale drug screening programs and clinical use, wherein >1 billion cells for each patient are needed to replace losses during heart attack, multiple sclerosis and diabetes. Producing this number of cells for one patient is challenging and a rethink is needed to scalable technology with the potential to meet the needs of millions of patients a year. Here we consider the role of materials discovery, an emerging area of materials chemistry that is in a large part driven by the challenges posed by biologists to materials scientists1-4.